(untitled) (Research, Society and Development, 2022)
Cryptococcosis is a fungal disease, which until the year 2020 was not compulsory notification, and until this period there were no exact data on its occurrence in Brazil. Objective: To analyze the clinical, laboratory, and epidemiological characteristics, beyond the spatial distribution and occurrence, of cryptococcosis in children living in the Brazilian Oriental Amazônia from 2000 to 2017. Methodology: This descriptive and transversal study was conducted at the University Hospital João de Barros Barreto (HUJBB), Belém-Pará, through data obtained from records of children aged up to 13 years old who were hospitalized with the diagnosis of cryptococcosis from 2000 to 2017. A descriptive analysis was performed using calculation of frequency, median age, and standard deviation using IBM SPSS 24.05.0. The significance level was set at p=0.05 (α=5%). The data were purified using the Table Win v. XX program. The laboratorial georeferencing of data for the creation of geographic data (BDGeo) was performed using ArcGIS 10.2 and TerraView 4.0. Results: Predominance infections happened in the rural areas, principally from C. gattii. Georeferencing demonstrated heterogenic distribution of the disease in mesoregions of Pará state, having a direct relation with deforested. Conclusion: The largest occurrence was in the northeastern mesoregion of Pará likely due to the environmental impact of deforestation.